Shifting the Aceh Regional Government System with a Sociological Approach to the Transformation of Local Political Habitus - Rizki Bima Anggara; Wicipto Setiadi; Irsyaf Marsal (Journal of Law Perspectives Review, 2026)
This study aims to analyze the shift in the Aceh regional government system following the enactment of Law Number 11 of 2006 on the Government of Aceh (LoGA) through a normative legal approach complemented by a sociological reading of the transformation of local political habitus. It also examines the implications of this legal transformation for the distribution of authority among the Aceh Government, the Aceh House of Representatives (DPRA), and the Central Government. This research employs a normative legal method using both the statutory approach and the conceptual approach. The analysis is based on primary legal materials, including relevant legislation, and secondary legal materials such as books, scholarly articles, and previous studies. These materials are analyzed qualitatively through the perspective of the sociology of law using Pierre Bourdieu's theory of habitus. The findings reveal that the LoGA has not only restructured Aceh's governance system by strengthening special autonomy and redistributing governmental authority but has also transformed local political habitus from a conflict-oriented and resistant disposition into a bureaucratic habitus characterized by institutional governance and democratic political participation. Furthermore, the redistribution of authority has reinforced the roles of the Aceh Government and the DPRA in regional governance while maintaining the supervisory and harmonization functions of the Central Government within Indonesia's national legal framework. This study concludes that the transformation of Aceh's governance system extends beyond formal legal reform, encompassing broader sociological changes that reshape political practices and power relations. Therefore, the effectiveness of Aceh's special autonomy depends not only on the legal authority granted but also on the capacity of governmental institutions to exercise that authority democratically, accountably, and in accordance with the principles of peacebuilding and the Unitary State of the Republic of Indonesia.